THE PALEOGENE SEDIMENT IN SOUTH SUMATRA - WHERE HAS IT GONE? - Eko Budi Lelono (Scientific Contributions Oil and Gas, 2004)
It has been widely known that South Sumatra Basin yields Paleogene successions (Ferdiyanto et al., 2003). These successions consist of Lemat and Talang Akar Formations (De Coster, 1974) or Lahat and Lower Talang Akar Formations (Clure et al., 2002). The regional stratigraphy of the South Sumatra Basin is shown in Figure 1. The Paleogene sediment is interpreted to form within the occurrence of horst and graben which was caused by the formation of Semangko dextral fault as a result of Late Cretaceous-Early Tertiary tectonism (Suwidiyanto, 2003). In its study, LEMIGAS (2001) classified these successions as the synrift deposit because they were deposited during rifting phase which presumably occurred in Oligo-Miocene age. In fact, finding the Paleogene synrift sediment in South Sumatra is a serious matter. Most studied wells provided by the client lacks biostratigraphic evidences of Paleogene age. The author contributed to this study by investigating the fossil contents of the studied sediment. The result of the biostratigraphic analysis of this sediment encourages the author to publish it as presented in this paper. Therefore, this paper is intended to disclose a comprehensive biostratigraphic data which is obtained from three different disciplines including foraminifer, nannoplankton and palynology. The Early Tertiary sediment in South Sumatra was generally deposited in the non-marine to transition (deltaic) environment (De Coster, 1973). The previous investigators show that this type of sediment contains rich palynomorph (Hasjim, 1993, Morley, 1995 and Lelono, 2003). Apparently, the age determination mostly referred to the occurrence of age diagnostic pollen. In this case, the appearance of peat swamp element of Meyeripollis naharkotensis is used to indicate the Oligocene sedi- ment (LEMIGAS, 1998). Unfortunately, it was lack of support from other microfossil study such as foraminifer and nannoplankton which resulted in least confidence to this interpretation. The occurrence of M. naharkotensis has been widely used to designate the Late Paleogene over the Southeast Asian Region (Morley, 1991 and Rahardjo et al., 1994). However, the stratigraphic range of M. naharkotensis is somewhat ambiguous as this pollen associates with the occurrence of coals indicating the ever-wet warm climate (Morley, 1991). In fact, this pollen ranges up as far as basal Late Miocene as recorded in the coaly succession of East Kalimantan (Lelono, 2003). On the other hand, in East Java, well section with least coal development shows the distribution of M. naharkotensis along the Oligocene section (Lelono, 2003). Nichols (1999) stated that the age indicators strongly controlled by facies reduce their stratigraphic value. This means that the occurrence of M. naharkotensis does not necessarily indicate the Late Paleogene. Therefore, it is suggested to consider the existence of coal lithology in applying M. naharkotensis for age interpretation. The occurrence of (?Late Oligocene)-Early Miocene rift sediments led to the conclusion that the rifting phase triggered by Late Cretaceous-Early Tertiary tectonism occurred slightly later in South Sumatra than that in Central Sumatra (LEMIGAS, 2001). Meanwhile, In Central Sumatra, rift deposit occurred during Eocene-Oligocene time (Williams et al., 1985 and Longley et al., 1990). Although De Coster (1974) assumed that South and Central Sumatra Basins had very similar and related history and could be considered as one large basin with many troughs and grabens, the recent biostratigraphic data suggest distinct period of basin development between South and Central Sumatra. This interpretation may not be obtained without accurate biostratigraphic data. Therefore, this paper is published to provide biostratigraphic information which allows explorationists to possess better understanding of the South Sumatra Basin.